Penolakan Pembayaran Tunai dalam Bertransaksi: Tinjauan Hukum Ekonomi Syariah pada Praktik Bisnis di Mulia Coffeenary - Desvrianto, Muhammad Rafi; Asyiqin, Hisyam; Nuroni, Abdul Muiz (CV. Social Politic Genius (SIGn), 2025)
Digital payment innovations have prompted business actors to implement exclusive non-cash transaction policies. However, this practice raises significant juridical and ethical problems. This research aims to critically analyze the policy of cash payment refusal through a case study at Mulia Coffeenary. The study employs an empirical legal research method, anchored by a primary review from the perspective of Sharia Economic Law. The results of the analysis indicate that this policy conflicts with the mandate of Rupiah sovereignty as outlined in Law Number 7 of 2011. Furthermore, the practice infringes upon the consumer’s right to choose, which is guaranteed by Law Number 8 of 1999. From a sharia review, the practice is found to be inconsistent with the principle of mutual consent (‘an tarāḍin minkum) in contracts and the legal maxim prohibiting harm (lā ḍarar wa lā ḍirār) to specific segments of society. It is concluded that the business rationale of efficiency and security cannot justify disregarding legal norms and transactional ethics. Therefore, this study recommends a model of coexistence between cash and digital payments to ensure broader financial inclusion and justice.